2020
DOI: 10.1007/s10815-019-01676-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of a novel c.630delG (p.Y211Tfs*85) mutation in NR5A1 gene in a Chinese boy with 46,XY disorders of sex development

Abstract: Purpose This study aimed to present the clinical features and gene mutation characteristics of a child with 46,XY disorders of sex development (DSD) caused by a novel heterozygous mutation in the NR5A1 gene to determine the potential association between this heterozygous mutation and the pathogenesis of 46,XY DSD. Methods We present the case of a Chinese child with ambiguous genitalia at birth but a normal adrenal gland. Targeted nextgeneration sequencing, comprising 163 candidate genes involved in sexual diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Fabbri et al [82] reported that loss-of-function mutations in the NR5A1 gene can lead to a 46,XY PGD phenotype with mild manifestations, dysgenetic testes, and preserved adrenal function. Similarly, Pan et al [52] reported the clinical characteristics and characteristics of the genetic mutation in an individual with 46,XY DSD caused by a new heterozygous mutation in the NR5A1 gene: c.630delG (p.Y211Tfs*85), presenting the case of a Chinese boy with ambiguous genitalia at birth and normal adrenal glands.…”
Section: Mutations In the Nr5a1 Genementioning
confidence: 95%
See 1 more Smart Citation
“…Fabbri et al [82] reported that loss-of-function mutations in the NR5A1 gene can lead to a 46,XY PGD phenotype with mild manifestations, dysgenetic testes, and preserved adrenal function. Similarly, Pan et al [52] reported the clinical characteristics and characteristics of the genetic mutation in an individual with 46,XY DSD caused by a new heterozygous mutation in the NR5A1 gene: c.630delG (p.Y211Tfs*85), presenting the case of a Chinese boy with ambiguous genitalia at birth and normal adrenal glands.…”
Section: Mutations In the Nr5a1 Genementioning
confidence: 95%
“…Similarly, several patients have also been described with a dicentric chromosome for the long arm of the Y chromosome (XYdic) [51], and this is usually associated with mosaicism and with an X0 cell line. Thus, in this group of disorders, various phenotypes can be seen, including normal males, individuals with ambiguous genitalia, male Ps [52], and patients with many of the stigmata of gonadal dysgenesis.…”
Section: Variants Of Gonadal Dysgenesismentioning
confidence: 99%
“…Mutations to SRY account for approximately 15% of 46,XY DSD [ 128 ]; while mutations in other genes such as NR5A1 or SOX9 are known to cause 46,XY DSD as part of a syndrome. To date, a genetic diagnosis is not achieved in around 50% of XY DSD cases [ 128 , 129 ]. Genetic diagnosis of ambiguous genitalia is particularly challenging and a clinical algorithm can facilitate this [ 130 ].…”
Section: Disorders Arising From Sox9 Mutations In Humansmentioning
confidence: 99%
“…A previous study identi ed a G35E substitution in the DBD region in a patient with 46, XY DSD presenting adrenal insu ciency along with moderately severe gonadal dysplasia, indicating that this variation results in serious adverse effects on NR5A1 function [20]. Additionally, the p.V15M, p.M78I, and p.G91S variations in this region are reportedly responsible for aberrant NR5A1 transcription, with the rst two variations resulting in altered subcellular localization [25]. Moreover, functional studies have shown that the p.S32N, p.N44del, and p.G91D variations in this region reduce the transactivation of cytochrome P450 family 11 subfamily A member 1 [23].…”
Section: Discussionmentioning
confidence: 97%